Lateinische Dialoge 1200-1400 Literaturhistorische Studie und Repertorium - Cardelle de Hartmann, Carmen (Mittellateinische Studien und Texte, 2007)
In this monograph the dialogue production between 1200 and 1400 is presented in a detailed repertory. Building on this material, the author describes four genres of dialogue (didactic, polemical, introspective and philosophical dialogues), locating them in the literary tradition.; Readership: All those interested in the literature of Late Antiquity and the (Latin) Middle Ages in Western Europe , as well as classical philologists and specialists on Renaissance literature and manuscript libraries.